POTENSI DAN TANTANGAN PEMBERDAYAAN MASYARAKAT LAHAN GAMBUT:: Studi Pendekatan Kehidupan Berkelanjutan di Kelurahan Tanjung Palas Kecamatan Dumai Timur Kota Dumai - Iwed Mulyani (KOMUNITAS, 2020)
Indonesia is a country with the largest area of ??tropical peatland land in the world. Riau Province has the largest peatland area (3.8 million hectares) in Indonesia. Besides having the largest land area, Riau Province is also the second-largest contributor to peatland fires (53,034 hectares) after Kalimantan with Dumai City as the region with the highest fire cases (15 cases). The trend in handling these problems has begun to involve relevant stakeholders, not just the responsibility of the government or the community, even the private sektor. One of the strategies undertaken is to analyze the potential that exists in peatlands using a continuous analysis to provide program recommendations that can solve this problem. Therefore this research will look at how the analysis of sustainable livelihoods conducted by PT Pertamina RU II Dumai company in providing recommendations for peatland community empowerment programs. This study uses qualitative research methods with data collection techniques using interviews, observation and documentation studies. The results of this study provide three program recommendations, namely the use of peatlands whit involving the Paman Jaya Mandiri Farmer Group, the improvement of the RT 12 RT toll road infrastructure, and the improvement of sanitation and PHBS counselingh